2001
DOI: 10.1097/00003246-200101000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid and plasma concentrations of nitric oxide metabolites in postoperative patients with subarachnoid hemorrhage

Abstract: The increase of cerebrospinal fluid nitrate after SAH may attribute to the endogenous nitric oxide production in the injured brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 7 publications
2
22
1
Order By: Relevance
“…Although we have no information regarding the presence of inducible NOS (iNOS) in our animals, this would seem plausible given the association between adenoviral vectors, inflammation, and iNOS induction in vascular smooth muscle cells and infiltrating leukocytes. 15,18 Further, SAH itself is associated with inflammation and increased CSF NO levels, [17][18][19][20][21] findings supported by our data. We believe that the larger elevation of CSF NO levels observed in AdeNOS-transduced dogs is a result of expression and activity of recombinant eNOS exclusively in these animals as indicated by our immunohistochemical and Western analysis data.…”
Section: Morphologysupporting
confidence: 86%
“…Although we have no information regarding the presence of inducible NOS (iNOS) in our animals, this would seem plausible given the association between adenoviral vectors, inflammation, and iNOS induction in vascular smooth muscle cells and infiltrating leukocytes. 15,18 Further, SAH itself is associated with inflammation and increased CSF NO levels, [17][18][19][20][21] findings supported by our data. We believe that the larger elevation of CSF NO levels observed in AdeNOS-transduced dogs is a result of expression and activity of recombinant eNOS exclusively in these animals as indicated by our immunohistochemical and Western analysis data.…”
Section: Morphologysupporting
confidence: 86%
“…eNOS catalyses the synthesis of NO, a regulator of basal vascular tone, cerebral blood flow, and smooth-muscle cell proliferation in the arterial endothelium [59]. Several studies have shown that the NO pathway is impaired and that NO levels in cerebrospinal fluid (CSF) are raised in animals following experimentally induced SAH [58]; moreover, the NO levels have been shown to increase in humans following aneurysmal SAH [60].…”
Section: Genetic Studiesmentioning
confidence: 99%
“…For example, ultrafiltered CSF was analyzed using commercial CE anion analysis reagents in studies of lupus or brain hemorrhage [142,143]. Directly injected CSF could be analyzed for nitrate and nitrite using a 100 mM borate buffer at pH 10.…”
Section: Cerebrospinal Fluidmentioning
confidence: 99%